Method for manufacturing a sample and method for observing a sample
Patent Information
- Application Number
- JP2021127590
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-30
- Filing Date
- 2021-08-03
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-08-03
AI Technical Summary
Existing observation methods using protective agents for electron microscopy result in the decomposition of organic compounds, leading to hydrocarbon gas contamination and material deformation or diffusion due to electron beam irradiation.
A manufacturing method involving the formation of a metal oxide or metal layer on the sample surface by reacting a gaseous metal compound with a gaseous oxidizing agent, using atomic layer deposition (ALD) to prevent material deformation and diffusion during electron beam exposure.
This method effectively suppresses material deformation and diffusion, maintaining observation accuracy and preventing contamination in electron microscopy.
Smart Images

Figure 00000018_0000 
Figure 00000019_0000 
Figure 00000019_0001
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a sample and a method for observing a sample.
Background Art
[0002] For example, Patent Document 1 describes a detection kit in which a material is coated with a protective agent containing at least one selected from a surfactant-containing solution, an amphiphilic compound, fats and oils, an ionic liquid, and osmium.
[0003] Further, Patent Document 2 describes an observation method including a step of applying a protective agent for electron microscope observation containing saccharides and electrolytes to a biological sample in a water-containing state.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Patent Document 2
Summary of the Invention
Problems to be Solved by the Invention
[0005] In the observation method using the detection kit described in Patent Document 1 and the observation method described in Patent Document 2, although they can be means for preventing the diffusion of elements brought to the sample and the deformation of the material, the organic compounds contained in the protective agent are decomposed by the observation method to generate hydrocarbon gas, and the generated hydrocarbon gas adheres to the sample or the observation device, thereby polluting the observation environment. For this reason, there has been a demand for a novel method for manufacturing a sample that can suppress the deformation of the material over time and the diffusion of elements of the material due to electron beam irradiation, and can prevent contamination caused by changes in the sample.
Means for Solving the Problems
[0006] To solve the above problems, a manufacturing method according to one aspect of the present invention is a method for manufacturing a sample for observation with an electron microscope, comprising: a first processing step of forming a layer of a metal compound by depositing a gaseous metal compound onto the surface of a material for manufacturing the sample; and a second processing step of forming a layer of metal oxide or metal from the layer of metal compound by reacting the metal compound with a gaseous oxidizing agent, wherein the material contains a first component that reduces the observation accuracy or deforms over time when exposed to an electron beam from an electron microscope. [Effects of the Invention]
[0007] According to one aspect of the present invention, it is possible to provide a novel method for manufacturing a sample and related technologies that can suppress deformation of the material over time, the diffusion of elements in the material due to electron beam irradiation, and prevent contamination caused by changes in the sample. [Brief explanation of the drawing]
[0008] [Figure 1] This figure illustrates the schematic of an atomic layer deposition (ALD) apparatus 10 for carrying out a manufacturing method according to one aspect of the present invention. [Figure 2] The images show a scanning transmission electron microscope (STEM) image of the thin section sample from Example 1, and the EDX spectrum obtained by scanning transmission electron microscope (STEM) in the corresponding region. [Figure 3] The images show a transmission electron microscope (TEM) photograph of a thin section of Comparative Example 1, and the EDX spectrum obtained by scanning transmission electron microscope (STEM) in the corresponding region. [Figure 4] These are scanning transmission electron microscope (STEM) images of the samples from Example 2 and Comparative Example 2. [Figure 5] These are scanning transmission electron microscope (STEM) images of the samples from Example 3 and Comparative Example 3. [Modes for carrying out the invention]
[0009] In this specification, when the term "sample" is used, unless otherwise specified, it means the entire object on which a layer of metal oxide or metal is formed on the surface of the material object by a manufacturing method according to one aspect of the present invention. Furthermore, when the term "material" is used, it means the entire object to be observed and is included in the "sample." The surface state of the "material" can be observed through the layer of metal oxide or metal formed on the "sample" using observation methods such as an electron microscope.
[0010] <Method for producing samples> A method for manufacturing a sample according to one aspect of the present invention is a method for manufacturing a sample for observation with an electron microscope, comprising: a first processing step of forming a layer of a metal compound by depositing a gaseous metal compound onto the surface of a material for manufacturing the sample; and a second processing step of forming a layer of metal oxide or metal from the layer of metal compound by reacting the metal compound with a gaseous oxidizing agent, wherein the material contains a first component that causes the observation accuracy of the sample to decrease over time or by receiving an electron beam irradiated by an electron microscope. Depending on the form of the material, the method for manufacturing a sample according to one aspect may also include a step of cutting the material to obtain a thin slice of the material.
[0011] 〔material〕 The observation sample may contain a first component and a second component. The first component is a material that causes a reduction in the observation accuracy of the observation sample when exposed to an electron beam from an electron microscope, and the second component is a component that has less impact on the observation accuracy of the observation sample than at least the first component. The first component may be a component that diffuses, deforms, and disappears when irradiated with an electron beam with an acceleration voltage of 30kV or higher during electron microscope observation. Furthermore, the first component may be a component that deforms, diffuses, or disappears over time, for example, within about 10 days after the material has been cut out. In other words, the first component has either the property of diffusing, deforming, and disappearing when irradiated with an electron beam, or the property of deforming, diffusing, or disappearing over time after the material has been cut out, or both.
[0012] [First ingredient] The reduction in observational accuracy caused by the first component is due to the diffusion, deformation, and / or disappearance of the first component resulting from the irradiation of a thin section of the material with an electron beam, or it occurs over time.
[0013] Diffusion can refer to the diffusion of elements as impurities within inorganic materials such as semiconductors, where a first component, contained as a dopant in an inorganic component, is diffused by an electron beam. It can also refer to the diffusion of fragments within or outside the material after a portion of the first component contained in a thinned material has decayed (also called fragmentation) by an electron beam. Furthermore, diffusion can refer to the diffusion of gases released outside the material by or without electron beam irradiation, as well as the diffusion of fine particles produced by decay within the material.
[0014] Deformation refers to the miniaturization or fragmentation of inorganic particles, which are the first component, either by or without electron beam irradiation. As a result, the miniaturized (degraded) inorganic particles or fragmented components can diffuse into or outside the material. In other words, deformation can be one aspect of diffusion accompanied by degradation.
[0015] Furthermore, "disappearance" includes the meaning that unfragmented components, or fragmented first components, diffuse due to heat and disappear from within the flaked material. In other words, disappearance can be one aspect of diffusion.
[0016] However, a reduction in observation accuracy can occur due to the diffusion, deformation, or disappearance of the first component. Furthermore, the diffusion, deformation, or disappearance of the first component may lead to the problem of being unable to observe the material containing the first component in its proper state.
[0017] The material to be observed may have a fine structure even in its thin slice. Here, the fine structure can be a multilayer structure or a sea-island structure having a continuous phase and a dispersed phase. Note that the material to be observed may include a layer with a sea-island structure having a continuous phase and a dispersed phase in one of the layers of the multilayer structure.
[0018] When the fine structure of the thin slice of the material is a multilayer structure, it is sufficient if at least one of the plurality of layers in the multilayer structure contains a first component. The multilayer structure of the thin slice of the material may have a thickness of about 0.001 μm to 10 μm for each layer.
[0019] When the fine structure of the thin slice of the material is a sea-island structure, it is sufficient if the first component is contained in either one or both of the continuous phase and the dispersed phase in the sea-island structure. The sea-island structure of the thin slice of the material may have an average particle diameter of the dispersed phase of about 1 nm to 1000 nm.
[0020] (Halogen) The first component can be a halogen or a component containing a halogen. Examples of the halogen itself include halogen doped as an impurity in an inorganic component.
[0021] As the first component, when a material containing a halogen is irradiated with an electron beam, diffusion of the halogen as a dopant, diffusion of a halogen gas, or diffusion of the halogen generated by fragmentation of the first component or a fragment containing a halogen may occur.
[0022] Examples of the component containing a halogen include silver halide, and the silver halide can be silver chloride, silver bromide, silver iodide, silver fluoride, and can be various silver halides having photosensitivity.
[0023] It should be noted that fluororesins can also be components that diffuse halogens through deformation. Fluororesins are not particularly limited as long as they can be used in various devices; for example, halogen-containing resins include fluororesins and chlorine-containing resins. Examples of fluororesins include polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride (PVDF), polytetrafluoroethylene, vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-trichloroethylene copolymer, vinylidene fluoride-vinyl fluoride copolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, and ethylene-tetrafluoroethylene copolymer. Examples of chlorine-containing resins include polyvinyl chloride and polyvinylidene chloride.
[0024] Furthermore, fluorine-based resins may also include fluorine-based ionomers. Fluorine-based ionomers are resins used as materials for proton-conducting polymer films, and in film / electrode assemblies, ionomers similar to those used in polymer films are employed as binders to bond the catalyst layer and the polymer film. More specifically, fluorine-based ionomers include, for example, ion-exchange polymers having sulfonic acid groups, and among these, fluorine-based polymers having sulfonic acid groups, such as perfluorosulfonic acid polymers, which have excellent proton conductivity, strength, and chemical stability. Specific examples of fluorine-based polymers having sulfonic acid groups include Nafion®, Flemion®, and Aciplex®.
[0025] (silver) The first component is silver, specifically silver particles, such as those used as metal catalysts or transparent electrode materials. A material containing silver particles as the first component may, after being thinned, deform into finer particles than before the thinned sample was prepared due to factors over time, resulting in diffusion within the material.
[0026] (lead) The first component may be lead and lead-tin alloy, which may be in particulate form, for example, a lead-tin alloy contained in solder. Lead and lead-tin alloy can be diffused and deformed by electron beam irradiation.
[0027] (organic compound) Examples of organic compounds as the first component include resins, surfactants, organic solvents, and plasticizers. Organic compounds can be deformed and diffused by electron beam irradiation. Some organic compounds may also diffuse outside the material flake even without being deformed by electron beam irradiation. If the material flake contains an organic compound, the organic compound may decompose and produce hydrocarbon gas. Hydrocarbon gas produced as fragments, and organic solvents that vaporize even without deformation, diffuse and reattach to the sample surface or observation equipment, causing contamination that contaminates the observation environment. Note that organic compounds may contain, for example, halogen atoms, nitrogen atoms, sulfur atoms, and oxygen atoms in their molecular structure, as long as they have hydrocarbon chains and / or aromatic rings containing carbon atoms and hydrogen atoms.
[0028] Examples of resins include those used as binders for inorganic particles, such as the fluoropolymer resins and fluoropolymer ions mentioned above.
[0029] Examples of non-fluorinated polymers include, specifically, polystyrene, polyarylene ethers such as polyetheretherketone, aromatic polyimides, polyphosphazenes, and aromatic polymers selected from polybenzoimidazole, in which the aromatic ring has been sulfonated. These may be composed as copolymers with olefins. Examples of cellulosic resins include cross-linked sulfoethylcellulose obtained by sulfoethylating cellulose, and these may be included in membrane electrodes.
[0030] Other resins include rosin, modified rosin, terpene resins, polystyrene, polyvinyl, and styrene-divinylbenzene copolymers, which may be included in soldering materials, for example.
[0031] Examples of surfactants include dispersants, wetting agents, defoamers, plasticizers, and leveling agents used when dispersing and mixing inorganic particles in a resin, and may be anionic surfactants, cationic surfactants, amphoteric surfactants, or nonionic surfactants.
[0032] More specifically, surfactants include glycerin fatty acid esters, sorbitan fatty acid esters, propylene glycol fatty acid esters, pentaerythritol fatty acid esters, trimethylolpropane fatty acid esters, polyoxyethylene glycerin fatty acid esters, polyethylene glycol fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, N,N-bis(2-hydroxyethyl) alkylamides, condensates of fatty acids and diethanolamine, alkyl sulfonates, sodium dicyclohexyl sulfosuccinate, polyoxyethylene alkyl phosphates, quaternary ammonium chlorides, alkyl betaines, alkylimidazolines, and alkylalanines. Surfactants are present in solder materials and can cause contamination.
[0033] Examples of organic solvents include alcohols such as ethanol and i-propanol, ketones such as acetone and methyl ethyl ketone, esters such as ethyl acetate, ethers such as dibutyl ether and 1,4-dioxane, aromatic solvents such as pyridine, chlorobenzene, toluene, and xylene, and hydrocarbon solvents such as hexane and cyclohexane. Organic solvents are included in solder materials as diluents and can cause contamination, diffusion, deformation, and disappearance.
[0034] Examples of plasticizers include phosphate ester plasticizers, terephthalic acid plasticizers, and adipic acid plasticizers.
[0035] (Sulfur compounds) Examples of the first component include sulfur compounds. Sulfur atoms contained in sulfur compounds can diffuse upon electron beam irradiation, which can lead to a reduction in observation accuracy. Examples of sulfur compounds containing sulfur atoms include elemental sulfur, sulfur oxides (SOx), hydrogen sulfide, and organic sulfur compounds.
[0036] [Second ingredient] The material and its flakes may contain a second component. The second component is a material that does not substantially diffuse, deform, or disappear due to electron beam irradiation or other factors over time. The second component may be a component that does not substantially diffuse, deform, or disappear even when irradiated with an electron beam with an accelerating voltage of 30kV to 300kV during electron microscope observation. Furthermore, the second component may be a component that does not deform, diffuse, or disappear over time, for example, up to about 10 days after the material has been cut.
[0037] If the microstructure of the material flake is a multilayer structure, it is sufficient that at least one of the layers in the multilayer structure contains the second component. Furthermore, if the microstructure of the material flake is a sea-island structure, it is sufficient that at least one of the continuous phase and the dispersed phase in the sea-island structure contains the second component.
[0038] The second component is one or more selected from glass, metal oxides, metals, and metal alloys, and is preferably selected from glass. Examples of glass include quartz glass, soda-lime glass, borosilicate glass, and organic glass. Examples of metal oxides include aluminum oxide, magnesium oxide, and hafnium oxide. The second component may also be a compound semiconductor such as silicon, sapphire, or GaAs (gallium arsenide), or a particulate semiconductor exhibiting fluorescence properties.
[0039] The second component may be a metal oxide such as titanium oxide, tin oxide, lead oxide, yttrium oxide, or indium oxide. These metal oxides may be used, for example, as a transparent electrode material and may be included in the flake in a layered or particulate form.
[0040] Furthermore, the second component may include a precious metal catalyst, which may include metal particles containing platinum group metals (PGMs) such as platinum catalysts, ruthenium catalysts, and ruthenium-platinum alloy catalysts.
[0041] The second component may also be a porous carbon support.
[0042] Furthermore, the second component may be an alloy containing tin and an element selected from the group consisting of gold, silver, silicon, bismuth, and antimony, and these can be included as alloys in solder materials.
[0043] The second component may include, for example, aluminum alloys, magnesium alloys, brass, bronze, iron armaco, iron carbonyl, and white metal, which may be included in the material in layered or particulate form.
[0044] Furthermore, the second component may be at least one selected from aluminum oxide (Al2O3), silicon oxide (SiO2), silicon oxide-aluminum oxide (SiO2-Al2O3), titanium oxide (TiO2), magnesium oxide (MgO), zeolite, ceria-zirconia composite oxide, zirconia, activated carbon, graphite, boron nitride, and carbon nitride. These may be included in the gas adsorption catalyst as catalyst supports.
[0045] The type of the second component is not limited, as long as it does not undergo substantial diffusion, deformation, or disappearance upon electron beam irradiation.
[0046] 〔material〕 Examples of materials include glass substrates containing layers of transparent electrode material used in touch panels, film electrodes used in fuel cells, semiconductors that constitute part of semiconductor chips, solder, photosensitive agents, and dispersions of semiconductor particles. Depending on whether the material is solid or liquid, a sample may be prepared by cutting out a portion of the material, or the sample may be prepared without cutting it out. The material only needs to contain at least a portion of the first component in a state prepared to the size for observation, and may also contain a second component.
[0047] The material used to prepare the sample only needs to contain the first component and is not limited to materials such as touch panels; it can be cut as a thin section from solar cells, organic EL materials, lenses, etc. In other words, the material can be, for example, the electrical and electronic device itself or a part of various composite materials used in the manufacture of electrical and electronic devices, and contains the first component which causes a reduction in observation accuracy when subjected to thinning treatment and / or electron beams by an electron microscope.
[0048] (Glass substrate) The material used in the method for manufacturing a sample according to one embodiment has a multilayer structure comprising multiple layers, and the first component may be a layer of a fluororesin such as vinylidene fluoride, or a fluorine-doped tin oxide film (FTO), and the multiple layers may have a second component comprising a layer of transparent electrodes and a layer of a glass substrate. Furthermore, the glass substrate may contain metal oxides such as titanium oxide, tin oxide, lead oxide, yttrium oxide, or indium oxide in the layer of transparent electrode material included as the second component.
[0049] When the glass substrate is a glass substrate for a touch panel, it may contain a vinylidene fluoride-based resin as a piezoelectric element. Furthermore, the glass substrate for the touch panel may have a fluorine-doped tin oxide layer as a transparent electrode layer. Alternatively, the glass substrate may have a fluorine-doped tin oxide film (FTO) layer as a transparent electrode layer. When such a glass substrate is irradiated with an electron beam, there is a problem that the fluorine doped into the transparent electrode material, or the fluorine present in the fluororesin, diffuses toward the glass substrate upon electron beam irradiation. According to a method for producing a sample in one aspect of the present invention, by performing ALD treatment on a thin piece of the glass substrate, the diffusion of the doped fluorine, or the fluorine present in the fluororesin, toward the glass substrate can be effectively prevented by electron beam irradiation.
[0050] (P-type semiconductor) The material used in the sample manufacturing method according to one embodiment may be, for example, a P-type semiconductor in which nitrogen, phosphorus, arsenic, and antimony are doped into silicon, and the P-type semiconductor is further doped with fluorine as an impurity. Such a P-type semiconductor may be a PMOS (P-channel metal oxide semiconductor) and may constitute part of a CMOS (complementary metal-oxide semiconductor). When observing the microstructure of a PMOS, applying an accelerating voltage to the P-type semiconductor causes the doped fluorine atoms to diffuse within the P-type semiconductor. Therefore, there is a problem in that it is not easy to observe the state of the PMOS more accurately with an electron microscope after doping with fluorine. According to the sample manufacturing method according to one embodiment of the present invention, by performing ALD treatment on a thin PMOS, the diffusion of fluorine atoms doped into the P-type semiconductor due to electron beam irradiation can be suitably prevented.
[0051] (membrane / electrode assembly) The material used in the method for producing a sample according to one embodiment may be a catalyst layer (sea-island structure) comprising, as a first component, silver particles (dispersed phase) and a fluororesin (continuous phase), wherein the fluororesin is a fluororesin ionomer, and as a second component, a carbon support, and may be a membrane / electrode assembly (multilayer structure) equipped with the catalyst layer. Instead of the fluororesin ionomer, a non-fluororesin ionomer may be included in the catalyst layer of the membrane / electrode assembly together with the silver particles. In solid fuel cells, the membrane / electrode assembly (MEA) is used as a membrane / electrode assembly comprising a polymer membrane and a catalyst layer, with catalyst layers (also called gas diffusion layers) provided on both sides of the polymer membrane. One of the catalyst layers functions as the cathode and the other as the anode. The catalyst layer may contain a carbon material as a second component.
[0052] Ionomers are resins used as materials for proton-conducting polymer films, and in film / electrode assemblies, ionomers similar to those used in polymer films are employed as binders to bond the catalyst layer containing porous material to the polymer film.
[0053] As the second component, the noble metal catalyst preferably consists of metal particles containing platinum group metals (PGMs), such as platinum catalysts, ruthenium catalysts, and ruthenium-platinum alloy catalysts, in the anode catalyst layer, and metal particles such as platinum catalysts, in the cathode catalyst layer. These are contained in the catalyst layers.
[0054] If the catalyst layer of a film / electrode assembly contains silver particles as a first component, there is a problem that after the catalyst layer is sliced, the silver particles deform and diffuse due to factors over time. Furthermore, if the catalyst layer contains a resin such as a fluorine-based ionomer, there is a problem that when the resin is irradiated with an electron beam, the resin deforms due to heat and diffuses. According to a method for producing a sample in one aspect of the present invention, by performing ALD treatment on a slice of the catalyst layer, deformation of silver particles (dispersed phase) and deformation and diffusion of resins such as fluorine-based ionomers due to electron beam irradiation can be effectively prevented.
[0055] (Soldering materials) Furthermore, the material may be a solder material. The solder material may be a solder material that contains an organic compound as a first component and an alloy containing tin and an element selected from the group consisting of gold, silver, silicon, bismuth, and antimony as a second component, or a solder material that contains a lead-tin alloy as a first component.
[0056] The solder material may be a solder paste used when mounting semiconductor chips on a printed circuit board, or it may be solder wire. Such a solder material may, for example, be subjected to electron microscopy observation after reflow in order to evaluate the relationship between its structure and its properties such as corrosion resistance and electrical conductivity. The solder material may contain a large amount of resin, also called flux, as well as a surfactant for adjusting coating and leveling properties, and an organic solvent. According to a method for producing a sample according to one aspect of the present invention, by performing ALD treatment on a thin piece of solder material, the deformation and diffusion of organic compounds contained in the solder material can be suitably prevented, thereby preventing a large amount of organic compound fragments or organic solvents from diffusing into the electron microscope due to electron beam irradiation and contaminating the electron microscope itself and the sample.
[0057] (Photosensitive agent) In the method for manufacturing a sample according to one embodiment, the material used may be a photosensitive agent. The photosensitive agent contains silver halide and an organic compound as a first component, and forms a layered film by being applied to a substrate by a known method. Even with such a photosensitive agent, when the state of the silver halide is observed by electron microscope observation, there is a problem that the silver is reduced by electron beam irradiation and halogen gas diffuses. According to the method for manufacturing a sample according to one embodiment, by performing ALD treatment on a thin piece of material containing the photosensitive agent, it is possible to prevent the diffusion of halogen gas from the photosensitive agent by electron beam irradiation.
[0058] (dispersion) In a method for producing a sample according to one embodiment, the material used may be a dispersion in which the above-mentioned second component is dispersed in an organic solvent. Examples of such dispersions include a dispersion of particulate semiconductors that exhibit fluorescence properties.
[0059] (Gas adsorption catalyst) The material used in the method for producing a sample according to one embodiment may be, for example, a gas adsorption catalyst. The gas adsorption catalyst may include an organic compound containing a sulfur atom as a first component, and may include at least one selected from alumina (Al2O3), silica (SiO2), silica-alumina (SiO2-Al2O3), titania (TiO2), magnesia (MgO), zeolite, ceria-zirconia composite oxide, zirconia, activated carbon, graphite, boron nitride, and carbon nitride as a second component.
[0060] Electron microscopy is sometimes used to evaluate how adsorbed gas molecules are distributed within a gas adsorption catalyst. However, sulfur compounds containing sulfur atoms may diffuse upon electron beam irradiation, making it difficult to observe the distribution of adsorbed gas molecules in their original state. According to one embodiment of the method for producing a sample, by performing ALD treatment on a thin piece of material containing a gas adsorption catalyst, it is possible to prevent the diffusion of sulfur atoms from the gas adsorption catalyst upon electron beam irradiation.
[0061] [The process of cutting thin slices from the raw material] A manufacturing method according to one aspect of the present invention may include a step of cutting thin slices from the material, depending on the form of the material, before performing the first step described later. The step of cutting thin slices from the material can be carried out by methods known in the art. Examples of pretreatment methods include cutting by focused ion beam (FIB), cutting by microtome, polishing by electrolytic polishing or chemical polishing, and thinning by Ar ion milling, and more preferably by focused ion beam (FIB) method.
[0062] The thickness of the thin slices obtained by the FIB (Focused Ion Beam) treatment process, which involves cutting thin slices from the material, is preferably 100 nm or less, more preferably 70 nm or less. The length × width of the thin slice is 5 μm. 2 ~100μm 2 It is acceptable as long as it is within the specified range.
[0063] For example, in FIB processing, a gallium (Ga) ion beam accelerated to several tens of kV is irradiated onto the material, causing a portion of the material to be cut out as a thin slice. The cut-out slice is then picked up by a manipulator.
[0064] Furthermore, in FIB processing, the thin sections cut out by irradiating with a gallium (Ga) ion beam may be subjected to processing such as argon milling.
[0065] Prior to FIB treatment, for example, a portion of the material may be pre-cut to a size suitable for FIB treatment using a diamond blade.
[0066] As described above, the thin sections cut by FIB treatment are subjected to ALD treatment.
[0067] [Atom Layer Deposition (ALD)] A manufacturing method according to one aspect of the present invention is a method for manufacturing a sample from a material by atomic layer deposition (ALD), and comprises a first processing step of forming a layer of a metal compound by depositing a gaseous metal compound onto the surface of the material, and a second processing step of forming a layer of metal oxide or metal from the layer of metal compound by reacting the metal compound with a gaseous oxidizing agent. The first and second processing steps may be repeated multiple times as a series of steps, as will be described later, and the series of steps may further include a step of supplying a purge gas.
[0068] The material may, for example, be subjected to the manufacturing method according to one embodiment while supported on a support. Here, the support is not limited as long as it can support the material, and examples include glass, metal, and resin plates, or petri dishes, meshes, or FIB grids. If the material is liquid, a mesh is preferred, and if the material is cut into thin flakes, an FIB grid is preferred. The FIB grid and mesh are preferably FIB grids that are generally used in electron microscope observation, and more preferably metal FIB grids or metal meshes made of gold, copper, nickel, molybdenum, and SUS (stainless steel). In addition, a coating may be formed on the mesh and FIB grid.
[0069] (ALD equipment) A method for producing a sample based on atomic layer deposition can be suitably carried out using the ALD apparatus 10 illustrated in Figure 1. The ALD apparatus 10 comprises a reaction chamber 11, a reduced pressure section 12, a precursor gas supply section 13, an oxidizing agent gas supply section 14, and a purge gas supply section 15.
[0070] A manufacturing method according to one embodiment includes a step of depositing a metal compound on the surface of a thin piece of material (first processing step) and a step of forming a layer of metal oxide by oxidizing the metal compound deposited on the surface with an oxidizing agent (second processing step), and these first and second processing steps are preferably carried out in a reaction chamber 11 provided in the ALD apparatus 10.
[0071] The reaction chamber 11 is independently connected to the reduced pressure section 12, the precursor gas supply section 13, the oxidizer gas supply section 14, and the purge gas supply section 15. The reaction chamber 11 is also equipped with a heating section (not shown), such as an infrared heater, which allows the temperature inside the chamber to be adjusted. In one embodiment of the manufacturing method, a layer of metal oxide is formed on the surface of the material by performing a first processing step and a second processing step.
[0072] The depressurization unit 12 is equipped with pumps such as a turbomolecular pump and a rotary pump. This allows the depressurization unit 12 to adjust the air pressure inside the reaction chamber 11 and to discharge unreacted metal compound gases, oxidizing agent gases, or purge gases remaining inside the reaction chamber 11.
[0073] The precursor gas supply unit 13 is equipped with a mass flow controller (MFC) that controls the flow rate and temperature of the metal compound gas, which is the precursor gas, thereby enabling control of the flow rate of the metal compound gas supplied into the reaction chamber 11.
[0074] The oxidant gas supply unit 14, like the precursor gas supply unit 13, is equipped with a mass flow controller (MFC), which allows control of the flow rate of the oxidant gas supplied into the reaction chamber 11.
[0075] The purge gas supply unit 15 supplies purge gas into the reaction chamber 11 and can control the flow rate of the purge gas.
[0076] In addition, it is preferable that the ALD apparatus 10 includes a control unit (not shown) and controls the reaction chamber 11, the reduced pressure unit 12, the precursor gas supply unit 13, the oxidizer gas supply unit 14, and the purge gas supply unit 15, respectively, so that a series of processes are repeated continuously.
[0077] [A series of steps] In one embodiment of the manufacturing method, the first processing step and the second processing step are included as a series of steps, and it is preferable to repeat this series of steps multiple times in the reaction chamber 11. This makes it possible to suitably adjust the thickness of the metal oxide layer deposited on the surface of the material flakes.
[0078] Furthermore, it is more preferable that the manufacturing method according to one embodiment includes a step of purging unreacted precursor gas from the reaction chamber 11 after the first processing step and before the second processing step (first purging step), and a step of purging unreacted oxidizing agent gas from the reaction chamber 11 after the second processing step and before the subsequent first processing step (second purging step). This prevents the accumulation of unreacted material on the surface of the material and allows for the formation of a more homogeneous metal oxide layer on the surface of the material.
[0079] In other words, from the viewpoint of the thickness of the metal oxide layer and the homogeneity of the layer, it is preferable that the manufacturing method according to one embodiment includes a first processing step, a first purging step, a second processing step, and a second purging step as a series of steps in the reaction chamber 11, and that this series of steps is repeated multiple times.
[0080] When the series of steps are carried out in the reaction chamber 11, the temperature inside the reaction chamber 11 is preferably maintained within the range of 20°C to 200°C, and more preferably within the range of 80°C to 150°C, in order to allow the metal compound to react suitably with the oxidizing agent. At this time, the atmospheric pressure inside the reaction chamber 11 is preferably maintained within the range of 200 mPa to 300 mPa.
[0081] Furthermore, it is preferable to repeat the series of steps 10 to 30 times in order to form a layer of metal oxide or metal of sufficient thickness.
[0082] (First processing step) The first processing step involves depositing a metal compound onto the surface of the material, thereby coating the surface of the material with the metal compound. The first processing step can be performed by placing the material S on the FIB grid 20, which is a support, and then placing the FIB grid 20 inside the reaction chamber 11 (Figure 1). Prior to performing the first processing step for the first time, the air inside the reaction chamber 11 may be purged with a purge gas after the FIB grid 20 has been placed inside the reaction chamber 11.
[0083] The metal compound used in the first processing step is a precursor of a metal oxide and is supplied in a vaporized state from the precursor gas supply unit 13 into the reaction chamber 11. The precursor metal compound can be any metal compound that can be vaporized (gasified) under a heated or reduced-pressure heated environment and that produces a metal oxide when reacted with an oxidizing agent. For example, it may contain metals such as hafnium (Hf), aluminum (Al), silicon (Si), zirconium (Zr), and titanium (Ti), and the metal may be a metal compound having a functional group selected from the group consisting of alkyl groups having 1 to 5 carbon atoms, alkoxy groups having 1 to 11 carbon atoms, halogens such as chlorine and bromine, and hydrogen.
[0084] Specific examples of these metal compounds include hafnium compounds such as tetrakishafnium, aluminum compounds such as diethylaluminum ethoxide, tris(ethylmethylamide)aluminum, aluminum sec-butoxide, aluminum tribromide, aluminum trichloride, triethylaluminum, triisobutylaluminum, trimethylaluminum (TMA), and tris(diethylamide)aluminum, silicon compounds such as tetramethoxysilane and SiH4, and titanium compounds such as tetraethoxytitanium. Among these, trimethylaluminum (TMA) is a more preferred metal compound because it can be suitably gasified in the reaction chamber 11 and reacts rapidly with the oxidizing agent. These metal compounds may be supplied into the reaction chamber 11 together with an inert gas such as nitrogen, for example.
[0085] It should be noted that the above-mentioned metal compounds may form metals rather than metal oxides, depending on their type and manufacturing conditions. Therefore, the "layer of metal oxide" described below can be interpreted as a "layer of metal," but for convenience, unless otherwise specified, the present invention will be described using only the "layer of metal oxide."
[0086] In the first processing step, when the precursor gas, a metal compound gas, is supplied to the reaction chamber 11, the OH groups present on the surface of the material react with the metal compound. The hydrogen atom of the OH group combines with one of the functional groups of the metal compound, producing by-products, while the oxygen atom derived from the OH group combines with the metal atom. At this time, the functional groups derived from the raw material metal compound are not completely removed, and the metal compound is chemically bonded to the surface of the material in a partially oxidized state. The by-products vary depending on the type of metal compound, but may include, for example, alkanes such as methane and ethane, alcohols such as ethanol, as well as halogens and hydrogen gas.
[0087] The amount of metal compound gas supplied in one first processing step can be appropriately adjusted according to the type and amount of material used in the manufacturing method, but it is preferably within the range of 0.5 to 1 SCCM. This allows sufficient amount of metal compound to be supplied into the reaction chamber 11 to consume the hydroxyl groups present on the surface of the material through the reaction. Furthermore, it is preferable to perform one first processing step for 1 to 5 seconds. This allows sufficient supply of metal compound to the surface of the material.
[0088] (First purging process) A manufacturing method according to one embodiment more preferably includes a step (first purging step) of purging unreacted metal compound gas as unreacted material from the reaction chamber 11 after the first processing step and before the second step. The first purging step can be performed by supplying purge gas from a purge gas supply unit 15 to the reaction chamber 11 and purging the purge gas from a reduced pressure unit 12. This makes it possible to discharge unreacted metal compound gas supplied into the reaction chamber 11 in the first processing step, as well as by-products generated by the reaction, to the outside of the reaction chamber 11. This effectively prevents oxide gas supplied in the subsequent second processing step from reacting with the unreacted metal compound gas remaining in the reaction chamber 11 and accumulating on the surface of the material.
[0089] Examples of purge gases include nitrogen, as well as noble gases such as argon and helium.
[0090] Furthermore, the amount of purge gas supplied in one first purge step is preferably within the range of 90 to 100 SCCM, and the process is preferably carried out for 5 to 50 seconds.
[0091] (Second processing step) In one embodiment of the manufacturing method, an oxidizing agent gas is supplied into the reaction chamber 11 from an oxidizing agent gas supply unit 14, and the oxidizing agent gas reacts with a metal compound chemically bonded to the surface of a thin piece of material. This forms a layer of metal oxide on the surface of the material.
[0092] The oxidizing gas supplied into the reaction chamber 11 in the second processing step is typically at least one selected from the group consisting of water vapor, ozone, and oxygen plasma. These oxidizing gases may also be supplied into the reaction chamber 11 together with an inert gas, such as nitrogen.
[0093] The amount of oxidizing agent gas supplied in one second processing step can be appropriately adjusted according to the type and amount of material used in the manufacturing method, but it is preferably within the range of 0.5 to 1 SCCM. This allows sufficient amount of metal compound to be supplied into the reaction chamber 11 to consume the hydroxyl groups present on the surface of the material through the reaction. Furthermore, it is preferable to perform one first processing step for 1 to 5 seconds. This allows sufficient supply of oxidizing agent gas to the surface of the material.
[0094] In the second processing step, when the oxidizing gas is supplied to the reaction chamber 11, it reacts with the metal compound deposited on the surface of the material. As a result, the functional groups of the metal compound are replaced with OH groups, and a layer of metal oxide is formed. At this time, the same by-products as those produced in the first processing step are generated.
[0095] (Second purging process) After the second processing step and before the subsequent first processing step, it is preferable to purge the oxidizing gas and by-products remaining in the reaction chamber 11 with an inert gas. The supply conditions for the purge gas into the reaction chamber 11 in the second purging step are the same as those for the purge gas supply in the first purging step, so no explanation is provided.
[0096] In addition, in the manufacturing method according to one embodiment, it is preferable that the series of steps be completed with the second purging step as the final step.
[0097] 〔sample〕 A sample produced by a manufacturing method according to one aspect of the present invention is a sample in which a layer selected from a layer containing metal oxides such as HfO2, Al2O3, SiO2, ZrO2, and TiO2, and a layer containing metals such as Ti and Si, coats the surface of the material.
[0098] Here, the thickness of the metal oxide layer formed on the sample is preferably in the range of 0.5 to 2 nm. This allows the sample to be used for clear observation of its surface state using an electron microscope.
[0099] As described above, a sample produced by the manufacturing method according to one embodiment can be suitably used, for example, as an observation sample.
[0100] <Observation Method> Observation samples produced by the manufacturing method according to one embodiment can be observed in detail using an electron microscope to determine their surface structure. The electron microscope used in the observation method according to one embodiment is preferably a transmission electron microscope (TEM) or a scanning transmission electron microscope (STEM), with a scanning transmission electron microscope (STEM) being more preferable. The scanning transmission electron microscope may also be a high-angle scattering dark-field scanning transmission electron microscope (HAADF-STEM) from the viewpoint that the type of atom can be confirmed based on the electron beam spectrum.
[0101] A transmission electron microscope irradiates a sample with an electron beam and forms an image of the electron beam that has passed through the sample onto a fluorescent screen using a magnetic lens. The contrast of the image can be obtained through diffraction contrast or absorption contrast, which utilizes the fact that the scattering angle of the electron beam differs depending on the density and crystal orientation of the material, or through phase contrast, which is obtained by interfering electron beams whose phase has been changed by the internal potential in the sample.
[0102] When observing samples using a scanning transmission electron microscope (STEM) or transmission electron microscope (TEM), the acceleration voltage is preferably in the range of 30 to 300 kV. This allows for optimal observation of the state of the thinned material while preventing diffusion, deformation, or disappearance of components contained in the material.
[0103] In addition, in one aspect of the observation method, elemental analysis can be performed by combining electron microscopy observation with energy-dispersive X-ray spectroscopy (EDX), electron energy loss spectroscopy (EELS), etc.
[0104] The present invention is not limited to the embodiments described above, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. [Examples]
[0105] [Evaluation of halogen diffusion] Thin sections were taken from glass substrates for touch panels by FIB treatment, and the thin section samples from Example 1, which underwent ALD treatment, and the thin section from Comparative Example 1 were observed under an electron microscope to evaluate halogen diffusion.
[0106] [Example 1] The thin section sample of Example 1 was obtained by performing ALD treatment on a thin section of multilayer composite material cut from a glass substrate.
[0107] (FIB processing) A glass substrate for touch panels (a laminate of metal layer / fluororesin layer / glass substrate) was obtained, and first, the glass substrate was cut out using a diamond blade (product name Isomet, manufactured by Bühler) to a size of 10mm x 10mm. Next, the cut glass substrate was further cut using a FIB apparatus to obtain a thin slice of multilayer composite material containing a transparent electrode (metal layer). The processing conditions in the FIB apparatus (product name Helios600, manufactured by FEI) and the size of the cut slice were as follows. Ga ion beam irradiation conditions: Acceleration voltage: 30kV Size of the cut thin section: 7 μm wide x 3 μm long x 0.0007 μm thick
[0108] (ALD treatment) Thin sections of the multilayer composite material obtained by FIB treatment were attached to a FIB grid (3 mm in diameter, copper grid, manufactured by Oken Shoji Co., Ltd.), and the TEM observation mesh was fixed in the reaction chamber of an ALD apparatus AT-400 (manufactured by Anric Technologies). The thin section sample of Example 1 was obtained by performing ALD treatment. The conditions for the ALD treatment were as follows. Precursor gas: Trimethylaluminum (TMA) Oxidizing gas: H2O Purge gas: N2 Reaction room temperature: 150℃ A series of processes consisting of a precursor gas treatment process, a precursor gas purging process, a steam gas treatment process, and a steam gas purging process was performed consecutively for one cycle, and this cycle was repeated 20 times, resulting in a total treatment time of 30 minutes. Precursor gas treatment: 0.5 seconds, TMA flow rate 0.75 SCCM Purge gas treatment: 8 seconds, purge gas flow rate: 96 SCCM Steam treatment: 0.5 seconds, steam flow rate 0.75 SCCM Purge gas treatment: 10 seconds, purge gas flow rate: 96 SCCM This series of processes was carried out in a reaction chamber at a temperature of 150°C and a vacuum of 225 mPa, repeated for 20 cycles, with a total reaction time of approximately 30 minutes. The ALD treatment yielded observation samples coated with a metal film of approximately 2 nm.
[0109] [Comparative Example 1] Thin sections of the multilayer material were cut from the same glass substrate used to prepare the thin section sample in Example 1, using a FIB apparatus under the same conditions as in Example 1, and these were used to obtain the thin section of Comparative Example 1. The thin section of Comparative Example 1 differed from the thin section of Example 1 in that it had not undergone ALD treatment.
[0110] (STEM observation) STEM observation was performed on the thin section sample of Example 1 and the thin section of Comparative Example 1 using a transmission electron microscope ARM200F (manufactured by JEOL Ltd.). The acceleration voltage for STEM observation was set to 200kV, and the observation magnification was set to 1,000,000x, and each sample was photographed. STEM images and elemental distribution spectra (EDX spectra) of ALD-treated thin section samples taken under these conditions are shown in Figures 2 and 3. Regions 1 and 2, indicated by dotted lines in Figures 2 and 3, respectively, are areas of the glass substrate constituting the thin section, and the spectra shown on the right side of the sample image in Figures 2 and 3, respectively, are the spectra in region 1 or region 2.
[0111] As shown in regions 1 and 2 of the thin section sample of Example 1 in Figure 2, no fluorine atoms were detected in the thin section sample of Example 1 observed after ALD treatment, even in areas other than the fluororesin film. In contrast, as shown in regions 1 and 2 of the thin section of Comparative Example 1 in Figure 3, fluorine atoms were detected in regions 1 and 2 of the thin section of Comparative Example 1 observed without ALD treatment, even in areas other than the fluororesin film. This confirms that ALD treatment can suppress the diffusion of fluorine atoms when observing thin section samples with a multilayer structure.
[0112] [Evaluation of silver diffusion] A coating was formed from a conductive resin material used for membrane electrode materials in fuel cells. Then, thin sections were taken by FIB treatment, and the thin section samples from Example 2, which underwent ALD treatment, and the thin section from Comparative Example 2, which did not undergo ALD treatment, were observed under an electron microscope.
[0113] [Example 2] First, a catalyst layer was formed by applying Ag paste (product name: conductive resin material, manufactured by ThreeBond Corporation) and drying it. Then, a portion of the catalyst layer was cut out using a FIB apparatus to obtain a thin slice of the catalyst layer. The thin slice sample of Example 2 was obtained by performing ALD treatment on the obtained thin slice.
[0114] (FIB processing) The processing conditions and the size of the cut sections in the FIB device (product name: Helios600, manufactured by FEI) were as follows. Ga ion beam irradiation conditions: Acceleration voltage: 30kV Size of the cut thin section: 7 μm wide x 3 μm long x 0.0007 μm thick
[0115] (ALD treatment) Thin sections of the catalyst layer material obtained by FIB treatment were placed on an FIB grid (3 mm in diameter, copper grid, manufactured by Oken Shoji Co., Ltd.), and the FIB grid was fixed in the reaction chamber of an ALD apparatus AT-400 (manufactured by Anric Technologies). By performing ALD treatment, the thin section samples of Example 2 were obtained. The conditions for the ALD treatment were as follows.
[0116] The FIB grid, on which the sample was placed, was fixed inside the reaction chamber of the ALD instrument AT-400 (manufactured by Anric Technologies), and ALD treatment was performed. The conditions for the ALD treatment were as follows: Precursor gas: Trimethylaluminum (TMA) Oxidizing gas: H2O Purge gas: N2 Reaction room temperature: 150℃ A series of processes consisting of a precursor gas treatment process, a precursor gas purging process, a steam gas treatment process, and a steam gas purging process was performed consecutively for one cycle, and this cycle was repeated 20 times, resulting in a total treatment time of 30 minutes. Precursor gas treatment: 0.5 seconds, TMA flow rate 0.75 SCCM Purge gas treatment: 8 seconds, purge gas flow rate: 96 SCCM Steam treatment: 0.5 seconds, steam flow rate 0.75 SCCM Purge gas treatment: 10 seconds, purge gas flow rate: 96 SCCM This series of processes was carried out in a reaction chamber at a temperature of 150°C and a vacuum of 225 mPa, repeated for 20 cycles, with a total reaction time of approximately 30 minutes. The ALD treatment yielded observation samples coated with a metal film of approximately 2 nm.
[0117] [Comparative Example 2] (Preparation of thin sections) The thin section of Comparative Example 2 was prepared under the same conditions as the thin section sample of Example 2, except that ALD treatment was not performed.
[0118] (STEM observation) STEM observation was performed on the same day and 10 days later for both the thin section sample from Example 2 and the thin section from Comparative Example 2.
[0119] STEM observation was performed on the thin section samples from Example 1 and Comparative Example 1 using a scanning transmission electron microscope (ARM200F, manufactured by JEOL Ltd.). The acceleration voltage for STEM observation was set to 200kV, and the observation magnification was set to 1,000,000x, and the samples were photographed.
[0120] Figure 4 shows STEM images of the thin section samples from Example 2 and Comparative Example 2, taken on the day of thinning and 10 days later, respectively. As shown in Figure 4, no deformation or diffusion of silver particles was observed in the thin section sample from Example 2 (with ALD), while deformation and diffusion of silver particles in the thin section of Comparative Example 2 were confirmed to have progressed after 10 days.
[0121] [Contamination assessment] The sample was dropped onto a mesh for a STEM electron microscope, and then the mesh was subjected to ALD treatment to prepare the observation sample for Example 3 and the sample for Comparative Example 3.
[0122] [Example 3] A 150-mesh STEM electron microscope mesh (3 mm diameter, copper mesh, manufactured by Oken Shoji Co., Ltd.) with a carbon thin film as an organic film was used as the substrate. ZnCuInS / ZnS Quantum Dots (manufactured by PlasmaChem) were dropped onto the mesh, and then the ZnCuInS / ZnS was subjected to ALD treatment.
[0123] (ALD treatment) The TEM observation mesh was fixed inside the reaction chamber of the ALD instrument AT-400 (manufactured by Anric Technologies), and the sample for Example 3 was obtained by performing ALD treatment. The conditions for the ALD treatment were as follows. Precursor gas: Trimethylaluminum (TMA) Oxidizing gas: H2O Purge gas: N2 Reaction room temperature: 150℃ A series of processes consisting of a precursor gas treatment process, a precursor gas purging process, a steam gas treatment process, and a steam gas purging process was performed consecutively for one cycle, and this cycle was repeated 20 times, resulting in a total treatment time of 30 minutes. Precursor gas treatment: 0.5 seconds, TMA flow rate 0.75 SCCM Purge gas treatment: 8 seconds, purge gas flow rate: 96 SCCM Steam treatment: 0.5 seconds, steam flow rate 0.75 SCCM Purge gas treatment: 10 seconds, purge gas flow rate: 96 SCCM This series of processes was carried out in a reaction chamber at a temperature of 150°C and a vacuum of 225 mPa, repeated for 20 cycles, with a total reaction time of approximately 30 minutes. The ALD treatment yielded observation samples coated with a metal film of approximately 2 nm.
[0124] (STEM observation) STEM observation of the sample from Example 3 was performed using a scanning transmission electron microscope ARM200F (manufactured by JEOL Ltd.). The acceleration voltage for STEM observation was set to 200kV, and the observation magnification was set to 5,000,000x. The observed sample was photographed. Figure 5 shows STEM images of the observed sample from Example 3, which was treated with ALD, and the sample from Comparative Example 3, which was not treated with ALD, under these conditions.
[0125] As shown in Figure 5, the electron microscope images of the observation sample formed from ALD-treated Quantum Dots (PlasmaChem) were clear, while the electron microscope images of the Quantum Dots (PlasmaChem) that were not ALD-treated were unclear. This confirms that ALD treatment can suppress contamination inside the STEM instrument and enable the acquisition of clear electron microscope images.
Claims
1. A method for producing a sample for observation by electron microscope, comprising the steps of: a first treatment step of depositing a gaseous metal compound on a surface of a material for producing the sample to form a layer of the metal compound; a second treatment step of forming a metal oxide or metal layer from the metal compound layer by reacting the metal compound with a gaseous oxidizing agent; A method for producing a sample, wherein the material includes a first component that reduces observation accuracy or deforms over time when exposed to an electron beam from an electron microscope.
2. 2. The method for producing a sample according to claim 1, wherein the first component is selected from silver, halogen, silver halide, lead, lead-tin alloy, fluorine-based resin, sulfur compound, and organic compound.
3. The material is Further comprising a second component other than the first component, The second component includes a layer of a transparent electrode material and a layer of a glass substrate. a layer containing the fluorine-based resin as the first component, the fluorine-based resin is a vinylidene fluoride-based resin, The method for producing a sample according to claim 2 , wherein the transparent electrode material is selected from tin oxide and indium oxide.
4. The material is Further comprising a second component other than the first component, the first component includes the silver particles and the fluorine-based resin; The second component includes a carbon support, 3. The method for producing a sample according to claim 2, wherein the fluorine-based resin is a fluorine-based ionomer.
5. The material is Further comprising a second component other than the first component, The first component includes the organic compound, the second component comprises an alloy containing tin and an element selected from the group consisting of gold, silver, silicon, bismuth, and antimony; The method for producing a sample according to claim 2 , wherein the organic compound includes at least one organic compound selected from a resin, a surfactant, and an organic solvent.
6. The material is The first component includes the lead-tin alloy and the organic compound, The method for producing a sample according to claim 2 , wherein the organic compound includes at least one organic compound selected from a resin, a surfactant, and an organic solvent.
7. the material is a dispersion containing the first component, The first component includes the organic compound, The method for producing a sample according to claim 2 , wherein the organic compound comprises at least one organic compound selected from a resin, a plasticizer, a surfactant, and an organic solvent.
8. The material is Further comprising a second component other than the first component, The first component includes the sulfur compound, As the second component, alumina (Al 2 O 3 ), silica (SiO 2 ), silica-alumina (SiO 2 -Al 2 O 3 ), titania (TiO 2 ), magnesia (MgO), zeolite, ceria-zirconia composite oxide, zirconia, activated carbon, graphite, boron nitride, and carbon nitride.
9. 9. The method for producing a sample according to claim 1, further comprising, before the first processing step, a step of cutting out a part of the material using a focused ion beam to obtain a thin slice of the material.
10. 10. The method for producing a sample according to claim 1, wherein the metal contained in the metal compound is any one metal selected from the group consisting of hafnium, zirconium, aluminum, silicon, and titanium.
11. The method for producing a sample according to claim 10, wherein the metal compound is trimethylaluminum.
12. 12. The method for producing a sample according to claim 1, wherein the gaseous oxidizing agent is at least one selected from the group consisting of water vapor, ozone, and oxygen plasma.
13. 13. The method for producing a sample according to claim 1, wherein in the first treatment step and the second treatment step, the metal compound and the oxidizing agent are reacted at a temperature in a range of 20°C to 200°C.
14. 14. The method for producing a sample according to claim 1, wherein the first processing step and the second processing step are repeated multiple times as a series of steps.
15. 15. The method for producing a sample according to claim 14, wherein the series of steps further includes a purging step of purging unreacted substances of the gaseous metal compound and unreacted substances of the gaseous oxidizing agent with an inert gas between after the first processing step and before the second processing step, and between after the second processing step and before the first processing step, respectively.
16. A manufacturing process for manufacturing a sample by carrying out the method for manufacturing a sample according to any one of claims 1 to 15; and observing the sample with an electron microscope.
17. 17. The method for observing a sample according to claim 16, wherein the electron microscope is a scanning transmission electron microscope or a transmission electron microscope.
18. 18. The method for observing a sample according to claim 16, wherein the sample is observed with the electron microscope at an acceleration voltage in the range of 30 to 300 kV.